Influence of light curing properties on composite resin polymerization: narrative literature review (Research, Society and Development, 2023)
Composite resins are used in tooth restoration to restore shape, function and aesthetics. The polymerization process of light-activated resins depends on light-curing devices, with several models on the market, each with its own characteristics, types of energy sources, variation in wavelength, type of pulse and light power. The objective was to carry out a narrative literature review regarding the types of photopolymerizers and the influence of their properties on the efficiency of polymerization of the composite resin. Bibliographical research was carried out in the Scielo, Google academic and Pubmed databases, using the 10-year period and the Portuguese and English languages ​​as a filter. The effectiveness and longevity of resins require adequate polymerization, which depends on the light energy emitted by light curing devices. Among the factors that interfere with polymerization are the power intensity of the photoactivator device (irradiance), the exposure time and the emitted wavelength. The surface on which the radiation is distributed must also be considered, in addition to a minimum light intensity and a wavelength compatible with that of the material's photoinitiator agent. Currently, there are halogen photopolymerizers on the market and those based on light emitted by diode (LED), among them the 1st, 2nd and 3rd generation, which is considered the most current technology used in the polymerization of composite resins. The resins have favorable properties, but their clinical success is closely related to the properties of light curing devices.